KAJIAN HUKUM ATAS LELANG TERHADAP BARANG JAMINAN FIDUSIA KENDARAAN BERMOTOR PADA PERUSAHAAN LEASING (STUDI PADA PT. SUMMIT OTO FINANCE CABANG MEDAN) - IRMA HANDAYANI SEMBIRING (PREMISE LAW JURNAL, 2015)
According to Article 29, paragraph (1), point b of Law No. 42/1990 on Feduciary Collateral, when there is a default, the settlement is prioritized by selling feduciary collateral through action. However, the Law gives another way out: when the highest price is not reached, it can be used underhanded selling. In the practice, however, although the creditor sells it underhandedly, he does not announce it in daily newspapers, and the length of time of selling is less than one month after the feduciary colletral is unsalabe in the auction. The creditor then sells it directly soon after he withdraws it from the auction. The execution of feduciary collateral on default debtors, basedLaw on Feduciary Colateral at PT Summit Oto Finance, Medan Branch, by withdrawing it from the facility of the acceptor or the people who submit the collateral. When within 7 (seven) days after the transfer of the collateral was not completed, it would be sold through actioning mechanism. The main obstacles in the execution of the feduciary collateral at PT Summit Oto Finance, Medan Branch, were that the collateral had been sold to the third party, the collateral had been pawned, and the collateral’s identity had been changed. Keywords: Collateral, Auction, Feduciary Collateral, Leasing